Comparison of the Traditional Chalkboard Lecture System with the Powerpoint Presentation: as a Teaching Technique for Medical Students - Deka Subha; Das Anandita; Ullah Kalim; Doungel Nomi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction:The emerging technologies made by day changing the techniques of teaching medical education. The teaching technique has changed since the last decade from the old traditional technique of chalk and talk (CNT) to a newer technique of Power-point presentation (PPT) to the video classrooms converting the whole traditional environment of the classrooms. This paper aims to access the perception of the medical students about these two instructional methods. Materials and methods: In this study cross-sectional descriptive survey was used. Medical students were selected through non-probability convenient sampling. The data were collected using a questionnaire-based survey about their views and perception of two lecture delivery methods, viz., PPT presentation, and using a chalkboard. For each of the two methods, the students were asked to rank twelve comments on a four-point scale: strongly agree, agree, disagree, or strongly disagree. The data was analyzed using SPSS version 16 and the results expressed as proportions. Results: In our study, more than 97% of our study respondents emphasized the value of chalk and talk and declared it a more effective and useful teaching tool in their learning experience than PowerPoint (86%) and recommended it for teaching. Conclusion: Both CNT, as well as PPT, are effective methods for medical education and both can be used in combination for the effective delivery of classroom sessions.